Sentinel Lymph‑Node Biopsy or Targeted Axillary Dissection in Node‑Positive Breast Cancer Patients Submitted to Neoadjuvant Therapy? - Sousa, Nuno (2025)
Introduction: Targeted axillary dissection (TAD) was designed for nodal staging in cN+ breast cancer (BC) patients submitted to neoadjuvant therapy (NAT). A recent study questioned the need to mark suspicious nodes pre-NAT. Methods: cT1-4 N1-2 BC patients scheduled for NAT were selected for retrospective appraisal. Patients were divided according with SLNB/TAD and ycN0/ycN+ status. Detection rate (DR), concordance rate (CR), predictive factors of successful clipped-node biopsy (CNB), sentinel node (SN) pathological complete response (pCR) and of additional non-sentinel lymph node (NSLN) involvement were assessed. Oncological outcomes were evaluated. Results: The study included 85 consecutive patients. DR was 83.6%, 98.8% and 98.8% for CNB, SLNB and TAD, respectively. CNB did not drive management changes as every CN was sentinel (CR 100.0%). CNB was unsuccessful in 10 patients with 2 (20.0%) re-operated with no additional benefit. Removal of at least 3 SN was associated with successful CNB (p=0.001). Fewer (1 vs 2) suspicious nodes at diagnostic echography and triple-negative or HER2 biological subtype were predictive of SN pCR. Lymph-vascular invasion was predictive of additional NSLN involvement in pSN+ patients (p=0.008). Disease-free survival was worse in ypSN+ (p=0.029) and the only regional recurrence was in an axillary lymph node dissection (ALND) patient. There was no difference in the overall survival between ALND and no-ALND patients (p=0.270). Conclusion: CNB is superfluous if 3 or more SN are retrieved using a dual mapping technique. It is safe to omit ALND if pCR of the SN is achieved. Future studies should assess the need for ALND in ypSN+ patients.